Growth, structural and electrical properties of AlN/Si (111) for futuristic MEMS applications. (1st March 2021) - Pandey, Akhilesh; Dutta, Shankar; Kaushik, Janesh; Gupta, Nidhi; Gupta, Garima; Raman, R.; Kaur, Davinder
Abstract: This paper presents the structural, optical, and electrical characteristics of AlN thin films on Si (111) substrate grown by DC magnetron sputtering technique for MEMS applications. The grown AlN thin films (thickness: 680, 900, and 1200 nm) exhibited polycrystalline wurtzite structure with preferred orientations along <001> directions. The mean grain size of the films varies from ~ (15–40 nm) of AlN layers. As the thickness increases, the FTIR E1 (TO) peak broadening of the films varies from 165 cm −1, 151 cm −1, and 128 cm −1, respectively. The electrical characterization of AlN/Si (111) is studied by fabricating the Metal-Insulator-Semiconductor (MIS) structure. The static dielectric constant of the AlN films varies from 6.80 to 5.94 as the films' thickness increases. The variation in dielectric constant values are due to the existence of interface trapped charges (interface trap density of states ~10 10 - 10 11  cm −2  eV −1 ) present in the AlN-silicon interface. The presented article corroborates the structural, morphological, optical, and electrical characteristics of AlN films on Si (111) with varying thickness comprehensively for piezoelectric MEMS applications.